Carbon–Carbon Bond Forming Reactions in Diazines via Transition-Metal-Catalyzed C–H Bond Activation - Gramage-Doria, Rafael; Bruneau, Christian (Synthesis, 2023)
An overview of the key achievements concerning C–C bond-forming processes with diazines (pyridazines, pyrimidines, and pyrazines) and benzodiazines (cinnolines, phthalazines, quinazolines, and quinoxalines) under transition-metal-catalyzed C–H activation is presented. The focus is on examples in which C–H functionalization takes place in the diazine or benzodiazine core because of the relevance of these compounds in material science and as active pharmaceutical ingredients. These metal-catalyzed protocols benefit from the biased reactivity of the C–H bonds targeted or from the presence of a rationally designed directing group proximate to the C–H bond to be functionalized. As such, innovative alkylations, alkenylations, alkynylations, arylations, and carboxylations are accomplished within such skeletons in a step- and atom-economy fashion.1 Introduction2 Transition-Metal-Catalyzed C–H Alkylation of Diazines3 Transition-Metal-Catalyzed C–H Alkynylation of Diazines4 Transition-Metal-Catalyzed C–H Alkenylation of Diazines5 Transition-Metal-Catalyzed C–H Arylation of Diazines6 Transition-Metal-Catalyzed C–H Carboxylation of Diazines7 Conclusion
Keywords: diazines; C–H activation; arylation; alkenylation; alkylation; metal catalyst